Statistical methods for hospital monitoring with R - Morton, Anthony Park, 1933-; Mengersen, Kerrie L.; Playford, Geoffrey; Whitby, Michael, 1950- (Chichester, West Sussex : Wiley, 2013)
Hospitals monitoring is becoming more complex and is increasing both because staff want their data analysed and because of increasing mandated surveillance. This book provides a suite of functions in R, enabling scientists and data analysts working in infection management and quality improvement departments in hospitals, to analyse their often non-independent data which is frequently in the form of trended, over-dispersed and sometimes auto-correlated time series; this is often difficult to analyse using standard office software. This book provides much-needed guidance on data analy.
Proportion -- Risk adjustment -- Cusum and related charts for binary data -- Introduction rate and count data -- Introduction, data, limitations of aggregated count data analysis -- Arranging data by weeks, months, quarters -- Multiple antibiotic-resistant organism (MRO) prevalence -- Overview of hospital quality improvement.
Includes bibliographical references and index.
Print version record and.publisher; resource not viewed.
Keywords: Hospitals -- Administration -- Statistical methods; Hospital Administration; Statistics as Topic; Efficiency, Organizational; Health services administration; Hospital administration; Statistics as topic; MEDICAL -- Hospital Administration & Care; Hospitals -- Administration -- Statistical methods; Electronic books; Electronic books